Crystallization of a bone-like apatite from a milk-containing revised simulated body fluid (SBF) - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2007)
Revised simulated body fluid (rSBF) was prepared using a conventional route but all the chemicals were dissolved in commercial cow milk instead of de-ionized water. To accelerate crystallization and increase the amount of precipitates, the influence of milk on the crystallization of calcium phosphates was studied in supersaturated solutions equal to 4 times the ionic concentrations of rSBF. The experiments were carried out in physiological conditions, i.e. pH of 7.35-7.40, temperature of 37.0 (+/- 0.2) degrees C, and duration of 7 days, using a constant-composition double-diffusion (CCDD) device, which enables slow precipitation in strictly controlled crystallization conditions. Similar experiments with 4 times the ionic concentrations of rSBF using de-ionized water as solvent were carried out as control. For comparison purposes, another set of experiments with 4 times the ionic concentrations of rSBF in de-ionized water also containing 40 g of bovine serum albumin (BSA) per liter was also conducted. The experimental results showed that the behavior of milk was similar to the presence of dissolved BSA. Some components of milk, presumably proteins, co-precipitated with calcium phosphates. This phenomenon had a strong negative influence on the crystallinity of the precipitates.
Keywords: revised simulated body fluid; calcium phosphates; bone-like apatite; milk; constant-composition double diffusion device; precipitation; mineralization; biomimetics